2016
DOI: 10.1186/s11671-016-1737-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Air Adsorption in Inverted Ultrathin Black Phosphorus Field-Effect Transistors

Abstract: Few-layer black phosphorus (BP) attracts much attention owing to its high mobility and thickness-tunable band gap; however, compared with the commonly studied transition metal dichalcogenides (TMDCs), BP has the unfavorable property of degrading in ambient conditions. Here, we propose an inverted dual gates structure of ultrathin BP FET to research the air adsorption on BP. In fabrication process of back-gate BP FET, BP was transferred directly onto a wafer covered with electrodes. Thus, we can exclude the BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The unchanged Raman spectra suggest that the PMMA capping can protect the BP flake from degradation effectively. In addition, it is known that the degradation can reduce the field effect mobilities by an order of magnitude [19,55,56]. Hence, a standard BP MOSFET was fabricated to investigate the protective effect of the PMMA layer.…”
Section: Resultsmentioning
confidence: 99%
“…The unchanged Raman spectra suggest that the PMMA capping can protect the BP flake from degradation effectively. In addition, it is known that the degradation can reduce the field effect mobilities by an order of magnitude [19,55,56]. Hence, a standard BP MOSFET was fabricated to investigate the protective effect of the PMMA layer.…”
Section: Resultsmentioning
confidence: 99%
“…Though the oxidation of BP caused by trace impurities such as water and oxygen in nitrogen gas during heating might take place, we attributed the self-separation of BP was the main reason for the sublimation instead of oxidationsublimation. The oxidation conditions have been widely studied before: Favron et al [41] first indicated that light, oxygen and water were three factors cause the oxidation of BP; Luo et al [18] reported that with 5% oxygen/Ar or 2.3% H 2 O/Ar, the oxidation rate is <5 Å for 5 h from XPS results; Wang et al [42] reported BP could remain stable in pure water without the presence of oxygen molecules from nuclear magnetic resonance spectroscopy results; Li et al [43] reported that heating could remove the metastable oxygen adsorbed on the surface of BP. Therefore, according to those studies on oxidation processes and mechanisms of BP, it could be concluded that with the protection of high purity (99.995%) nitrogen gas, the sublimation of BP in this work could be described as a physical process of layer separation.…”
Section: Uniform Color Changes With No Observable Cracks During the I...mentioning
confidence: 99%
“…here we eliminated the oxidation of BP as the main factor facilitating sublimation. Favron 39 first indicated that light, oxygen and water were the three factors cause the oxidation of BP; Luo 17 reported that with 5% oxygen/Ar or 2.3% H 2 O/Ar, the oxidation rate is < 5Å for 5h from XPS results; Wang 40 reported BP could retain stable in pure water without the presence of oxygen molecules from nuclear magnetic resonance (NMR) spectroscopy results; Li 41 reported that annealing could remove the metastable oxygen adsorbed on the surface of BP. Hence according those studies on oxidation mechanism of BP, as well as considering protection of high purity (99.995%) nitrogen gas in this work, we attributed the self-separation of BP was the main reason for the sublimation.…”
Section: Uniform Color Changes With No Observable Cracks Were Observementioning
confidence: 99%
“…Despite all of the advantageous properties, the lack of stability under ambient conditions limits further study of BP and its implementation. The previous research on degradation of BP proved that BP starts to degrade immediately once exposed to oxygen, water, and light, resulting in the formation of “bubbles” on the surface of BP. Especially, oxygen plays a critical role in the degradation process and changing the properties of BP; theoretically, oxygen molecules change the BP surface hydrophilic so that water can easily interact with the oxidized surface . The degradation process has been observed as follows.…”
Section: Introductionmentioning
confidence: 99%